Urinary trace metals in association with fetal ultrasound measures during pregnancy. Issue 2 (11th April 2020) - Kim, Stephani S.; Meeker, John D.; Aung, Max T.; Yu, Youfei; Mukherjee, Bhramar; Cantonwine, David E.; McElrath, Thomas F.; Ferguson, Kelly K.
Abstract : Supplemental Digital Content is available in the text. Abstract : Toxic metals have been associated with lower birth weight while essential metals have been associated with higher birth weight. Evidence for other metals is either inconsistent or limited in terms of number of studies. This study analyzed 17 urinary metals, individually and as a mixture, and their association with measures of fetal growth in the LIFECODES birth cohort. Ultrasound was used to measure the abdominal circumference, head circumference, and femur length and measures were used to calculate estimated fetal weight at ~26 and ~35 weeks. We calculated the z score based on gestational age at scan, and estimated fetal weight (EFW) was combined with birth weight for longitudinal analyses. Metals were measured in samples collected at ~26 weeks. We used linear mixed-effects models to examine associations between metals and repeated measures of each outcome, controlling for covariates. Principal components analysis reduced the biomarkers to predictors that may share some commonality. We found that an interquartile range increase in selenium was inversely associated with femur length z score as well as other growth outcomes. Other essential metals, however, were associated with an increase in growth. Finally, the PCA component comprised of arsenic, mercury, and tin was associated with decreased head circumference z score (−0.14 [95% CI, −0.23, −0.05]).